P427 LATE TREATMENT OF A CASE OF PULMONARY ARTERY HYPOPLASIA. (18th May 2022) - Parodi, A; Trocchio, G; Camerini, A; De Caro, E; Lupi, G
Abstract: Here we want to present the case of a woman who came to our observation for the onset of dyspnea due to exertion. It is a subject followed from a young age for a congenital malformation of the urinary tract. At that time the presence of stenosis of the branches of the pulmonary artery associated with an interventricular septal defect was accidentally diagnosed; however the blood pressure values in the pulmonary artery were within the limits, so no interventional therapy was undertaken. In the following years the patient developed systemic arterial hypertension associated with renal failure for which medical therapy was started and an annual follow–up was scheduled. Over the years various echocardiographic checks were repeated without ever finding high pressures in the pulmonary artery. At the last check, performed precisely for the onset of dyspnea from exertion, the estimated systolic pressure in the pulmonary artery was equal to 100 associated with a dilation of the right ventricle with hypertrophy, hepatomegaly was also present in the absence, however, of signs of peripheral congestion. The catheterization of the right heart confirmed the presence of severe precapillary pulmonary hypertension and the CT scan with three–dimensional reconstruction highlighted the almost total agenesis of the left lung branch thus revealing the presence of a pulmonary hypertension of the fourth group, also supported by the negativity of the other tests proposed in the diagnostic work of the ESC Guidelines. In agreement with a national reference center for the treatment of pulmonary hypertension, we started Bosentan therapy with increasing dosage up to the target dose and long–term oxygen therapy. After four months of follow–up, the patient shows an improvement in functional capacity and the haemodynamic data remain stable. To our knowledge there are only the experiences of single centers regarding the treatment of forms of pulmonary hypertension due to anatomical malformations of the pulmonary circulation and for this reason medical therapy is not standardized. This subset of patients represents a challenge for the clinician as hypertension can be secondary both to the lack of part of the vascular bed and to reactive hyperplasia of the endothelium of the remaining circulation due to parietal stress due to pressure overload.